Biochemical and Histopathological Studies of Key Tissues in Healthy Male Wistar Rats Fed on African Yam Bean Seed and Tuber Meals - Omena Bernard Ojuederie; John Adebayo Ajiboye; Olubukola Oluranti Babalola (Journal of Food Quality)
Food insecurity and malnutrition are currently major issues affecting most developing countries, especially on the African continent. To mitigate this effect, focus is being given to orphan or underutilized crops with immense potentials to boost food and nutrition security in Africa, such as the African yam bean (AYB) Sphenostylis stenocarpa. The effect of AYB seed and tuber meals on the tissues of the kidney, liver, and testis of healthy male Wistar rats were investigated in this study. Four accessions of AYB were used for this study, TSs 107, TSs 140, AYB 45, and AYB 57. Thirty rats were randomly assigned into five groups (n = 6). Group I was fed on standard pelletized rat chow (control), Group II fed on 50% seed meal, Group III fed on 100% seed meal, Group IV fed on 50% tuber meal, and Group-V fed on 100% tuber meal. At the end of the treatments, the animals were sacrificed after 72 h under light ether anesthesia, and biochemical and histopathological analyses were conducted on the tissues. Phytate concentration was higher in the seeds (TSs140 (550 mg 100g−1), AYB45 (460 mg 100g−1), and AYB57 (485 mg 100g−1)) compared to the tubers (TSs140 (14.8 mg 100g−1), AYB 45 (275 mg 100g−1), and AYB57 (240 mg 100g−1)). The consumption of 100% unprocessed AYB seeds caused liver and kidney damage in rats due to increased levels of aspartate aminotransferase (5.04 ± 1.62 U L−I), alanine aminotransferase (8.46 ± 2.43 U L−I), and lipid peroxidation (0.27 ± 0.02-unit mg−1protein). AYB tubers were innocuous to Wistar rats investigated. Good processing of AYB seeds is required for safe consumption by humans and livestock. This study has shown that tubers of AYB are safe for human consumption and should be utilized in meals as it contains fewer antinutrients and had no significant effect on the tissues examined in Wistar rats.